ANALISIS MISKONSEPSI PADA MATERI LARUTAN PENYANGGA SISWA KELAS XI IPA MA SWASTA DARUL ULUM KUBU RAYA - Abdul Chozim (Universitas Muhammadiyah Pontianak, 2018)
The problems faced by the students in chemistry class, especially in Buffer Solutions, often caused a misunderstanding. Continuous misunderstanding can lead to a misconception. This study aimed to analyze the misconceptions in Buffer Solutions among the eleventh grade students of MA Darul Ulum Kubu Raya 2016/2017 using a Diagnostic Test instrument. Using a descriptive method, the data revealed collected by employing 10 items of multiple choice with their reasons. The study revealed that the misconceptions in Buffer Solutions occurred in all concepts. The most common misconception took place in the indicator of explaining how the base buffer solution works when it is added by a small amount of alkaline (80%). The lowest happened on the indicator of determining the mixture of compoundsof the acid buffer solution (31%). The misconception that occured in each indicator was 70.4%. The misconception was caused by the students’ associative thinking skills was 48.4%. Therefore, the factors related to misconceptions faced by the students in Buffer Solutions are the lack of understanding, the learning methods applied by the teacher, and the reference books, particularly the non-school text books.